Factors controlling the selectivity for Na+ over Mg2+ in sodium transporters and enzymes. Issue 25 (14th June 2016) - Dudev, Todor; Mazmanian, Karine; Lim, Carmay
Abstract : The paper discloses the key factors and physical bases that render a given binding site either Mg 2+ or Na + -selective. Abstract : Na + and Mg 2+ play different crucial roles in biological systems. Both cations are present in comparable amounts in the cytosol, but how monovalent Na + can compete with the divalent Mg 2+, which can better accept charge from negatively charged ligands, in sodium transporters/enzymes has not been investigated. Hence, it is not clear how Na + and Mg 2+ -binding sites have evolved to discriminate the "right" cation among non-cognate ones from the surrounding milieu and the physical basis governing the selectivity for Na + over Mg 2+ . The results, which are consistent with available experimental data, reveal that in proteins, the selectivity for Na + over Mg 2+ in sodium-binding sites stem mainly from the size, charge, and charge-accepting ability differences between Na + and Mg 2+ . A protein could achieve Na + selectivity by (i) reducing the number of metal-ligating ligands, (ii) maintaining an optimal balance of different ligating-strength ligands whose interactions in the metal-binding site would favor Na + over rival mono/divalent cations, (iii) increasing the solvent exposure of the metal-binding site, or (iv) increasing binding site rigidity forcing Mg 2+ to adopt the coordination distances/geometry of Na + . Sodium-binding proteins use one or more of these factors to achieve Na + selectivity.